Demystifying the book of Revelation - Burton, William; Paraclete Video Productions (Orleans, MA : Paraclete Press, 2015)
"Difficulties of understanding aside, Fr. Bill explains that the message of the book of Revelation, while confusing to us, was clear to early Christians: Rome is evil, Christians should withdraw from Roman society, and they should do so knowing that it will cost them dearly. Christian non-involvement and passive resistance will ultimately result in victory, but such a victory, like Christ's, may include suffering persecution and death."--Back of container.
The Genre of Apocalyptic Literature and How to "Read" It -- Jewish Sources, Like the Book of Daniel, that Inspired Revelation's Author -- The Basics: Who wrote Revelation? When? What does the book say? -- What Makes this Book So Attractive to So Many? -- The Erroneous "Rapturist" Interpretation -- A Better Understanding.
Title from container.
DVD.